Deciphering the impact of cerebrospinal fluid on stem cell fate as a new mechanism to enhance clinical therapy development - Radoszkiewicz, Klaudia; Bzinkowska, Aleksandra; Chodkowska, Magdalena; Rybkowska, Paulina; Sypecka, Monika; Zembrzuska-Kaska, Ilona; Sarnowska, Anna (Frontiers in Neuroscience, 2024)
Neural stem cells (NSCs) hold a very significant promise as candidates for cell therapy due to their robust neuroprotective and regenerative properties. Preclinical studies using NSCs have shown enough encouraging results to perform deeper investigations into more potential clinical applications. Nevertheless, our knowledge regarding neurogenesis and its underlying mechanisms remains incomplete. To understand them better, it seems necessary to characterize all components of neural stem cell niche and discover their role in physiology and pathology. Using NSCs in vivo brings challenges including limited cell survival and still inadequate integration within host tissue. Identifying overlooked factors that might influence these outcomes becomes pivotal. In this review, we take a deeper examination of the influence of a fundamental element that is present in the brain, the cerebrospinal fluid (CSF), which still remains relatively unexplored. Its role in neurogenesis could be instrumental to help find novel therapeutic solutions for neurological disorders, eventually advancing our knowledge on central nervous system (CNS) regeneration and repair.